Functionalized multi-walled carbon nanotubes based Newtonian Nano fluids for medium temperature heat transfer applications. (August 2019) - Yellapu, Gandhi; Chachin Vishal, C.V.; Kandoth, Madithil Pramod; Saha, Priyanka; Bojja, Ramachandra Rao; Gandham, Sriganesh; Kanaparthi, Ramesh
Highlights: Stable medium temperature Nano thermic fluids (MNTFs) prepared by using functionalized MWCNTs. Thermal conductivity and specific heat capacity were enhanced by optimum nanoparticle addition. Detailed thermo-physical characterizations have been made. Cycle stability has been studied by solar test loop. Abstract: Functionalized multi-walled carbon nanotubes (f-MWCNTs) were synthesized and dispersed in the organic heat transfer fluids (OHTFs) to improve the thermo-physical properties of the medium temperature stable Nano thermic fluids (MNTFs). The prepared MNTFs showed an enhancement in thermal conductivity especially at high temperatures compared to the base OHTFs with addition of low quantities of f-MWCNTs. Based on the rheological studies, the Newtonian behaviour of the synthesized MNTFs have been demonstrated over a wide range of shear rates at various temperatures. The present study thus confirms the potential of developed MNTFs with desired rheological properties, high thermal and mechanical stability, high flash point, high specific heat capacity and high thermal conductivity for medium temperature heat transfer applications. The developed MNTFs were found to exhibit high and stable dispersion even after centrifugation with a speed of 5000 rpm for 30 min.